2005
DOI: 10.1097/01.ccm.0000182817.20977.e9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increased cardiac output on hepatic and intestinal microcirculatory blood flow, oxygenation, and metabolism in hyperdynamic murine septic shock

Abstract: During murine septic shock achieving normotensive hyperdynamic hemodynamics with fluid resuscitation and norepinephrine, exogenous glucose requirements together with the lack of norepinephrine-induced increase in the rate of gluconeogenesis mirror impaired metabolic capacity of the liver despite well-maintained hepatosplanchnic microvascular perfusion and oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 53 publications
2
37
0
1
Order By: Relevance
“…Tao et al (39) have shown that cardiac function was significantly reduced in CLP mice with fluid resuscitation. Albuszies et al (1) reported that a combination of fluid resuscitation and norepinephrine resulted in significantly increased cardiac output in CLP-induced septic mice. Collectively, these data suggest that prevention of cardiac dysfunction could be an important strategy in management of septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Tao et al (39) have shown that cardiac function was significantly reduced in CLP mice with fluid resuscitation. Albuszies et al (1) reported that a combination of fluid resuscitation and norepinephrine resulted in significantly increased cardiac output in CLP-induced septic mice. Collectively, these data suggest that prevention of cardiac dysfunction could be an important strategy in management of septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Systolic blood pressure was read in anesthesia after catheterization of the carotid artery (Albuszies et al, 2005) in mice loaded with IgE on the previous day. After intravenous antigen challenge, the mean blood pressure rose from $95 mm Hg to $170 mm Hg within 2 min, followed by a sudden and massive drop to $60 mm Hg, from where it slowly recovered ( Figure 3A).…”
Section: Ablation Of Connective Tissue Mast Cells By Expression Of Crmentioning
confidence: 99%
“…Nevertheless, this technique reflected the effect of iloprost on microcirculation by showing significant differences between treatment groups and the control group and between the different treatment groups. This method has not been used in pig IECR thus far, but measurements in mouse livers 13 and pig 15 and human 29 intestinal mucosa during sepsis episodes have been performed, providing evidence that microcirculatory disturbances can be measured. Ischemia-reperfusion, reflected by compromised nutritional perfusion and leukocyte adherence, can be decreased significantly by prostacyclin donor bolus pretreatment, as shown previously in a rat liver transplant model using intravital microscopy for microcirculatory measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The technique and reliability testing were described previously. [13][14][15][16][17] Microvascular blood flow (recorded in arbitrary units [AU]) was derived from the power spectra of back scattered laser light representing the distribution of Doppler shifts of the erythrocyte velocities. The rHb and SO 2 values were derived from light spectra detected after tissue illumination and back scattering.…”
Section: Assessment Of Microcirculationmentioning
confidence: 99%